N-terminal pro-brain natriuretic peptide improves the C-ACS risk score prediction of clinical outcomes in patients with ST-elevation myocardial infarction. Issue 1 (December 2016) - He, Peng-cheng; Duan, Chong-yang; Liu, Yuan-hui; Wei, Xue-biao; Lin, Shu-guang
Abstract Background It remained unclear whether the combination of the Canada Acute Coronary Syndrome Risk Score (CACS-RS) and N-terminal pro-brain natriuretic peptide (NT-pro-BNP) could have a better performance in predicting clinical outcomes in acute ST-elevation myocardial infarction (STEMI) patients with primary percutaneous coronary intervention. Methods A total of 589 consecutive STEMI patients were enrolled. The potential additional predictive value of NT-pro-BNP with the CACS-RS was estimated. Primary endpoint was in-hospital mortality and long-term poor outcomes. Results The incidence of in-hospital death was 3.1%. Patients with higher NT-pro-BNP and CACS-RS had a greater incidence of in hospital death. After adjustment for the CACS-RS, elevated NT-pro-BNP (defined as the best cutoff point based on the Youden's index) was significantly associated with in hospital death (odd ratio = 4.55, 95%CI = 1.52–13.65, p  = 0.007). Elevated NT-pro-BNP added to CACS-RS significantly improved the C-statistics for in-hospital death, as compared with the original score (0.762 vs. 0.683, p  = 0.032). Furthermore, the addition of NT-pro-BNP to CACS-RS enhanced net reclassification improvement (0.901, p  < 0.001) and integrated discrimination improvement (0.021, p  = 0.033), suggesting effective discrimination and reclassification. In addition, the similar result was also demonstrated for in-hospital major adverse clinical events (C-statistics: 0.736 vs. 0.695, p  = 0.017) or 3-year mortality (0.699 vs. 0.604, p  = 0.004). Conclusions Both NT-pro-BNP and CACS-RS are risk predictors for in hospital poor outcomes in patients with STEMI. A combination of them could derive a more accurate prediction for clinical outcome s in these patients.